I hate my bow! - Wilhelm, Hans, 1945- (New York : Scholastic, 1995)
A little dog laments the fact that the other dogs won't play with him as long as he has a bath, a bow, and a chain.
Level 1
Keywords: Play -- Fiction; Dogs -- Fiction